Effect of surface treatment on the micro-shear bond strength to zirconia - Esam Tashkandi (Saudi Dental Journal)
The constant quest for finding the ultimate esthetic dental restorative material has led to numerous alternatives. These materials, in addition to possessing optical properties simulating natural teeth, should also have physical properties that can withstand the harsh oral environment. Due to their greater toughness, zirconium oxide materials have been used as a core material for all-ceramic restorations. Objective: The objective of this study was to evaluate the resin-composite micro-shear bond strength to zirconia using different techniques of surface treatment. Materials and methods: Fully sintered zirconia (LAVA, 3M-ESPE, Seefeld, Germany) discs were used in combination with resin-composite (Filtek Supreme, 3M-ESPE, Seefeld, Germany) discs and divided into four groups of surface treatments. The micro-shear bond strength was measured by applying an axial load on the bonded interface until failure occurred. Failure load (N) was determined and the samples were examined under a SEM and the failure type was identified. One-way analysis of variance (ANOVA) was used to analyze the data with the level of significance α = 0.05. Results: Data analysis revealed significant difference between the different tested surface treatments with the group using sandblasting and coated with an experimental primer showing the highest failure load and a cohesive fracture pattern. Conclusion: Within the limitations of this in vitro study the use of an experimental primer achieved a better bond strength in combination with air-abrasion particles. Keywords: Zirconia, Micro-shear bond strength